Strategic Analysis of Tata Motors in the United Kingdom: Recommendations for Nigeria Market - Adeniran, Adetayo Olaniyi; Awe, Gbenga Titus (Management Analytics and Social Insights, 2025)
Evidence has revealed that Tata Motors has been successful in recent years by grasping foreign opportunities. The money earned from overseas locations was about 9% in 2016; in the two years, it rose to 79.80% in 2018. The bendy strategy framework is employed to assess the strategies adopted by Tata Motors in a selected country, which enhanced to acquire a global presence in the automotive manufacturing sector, mainly in the United Kingdom. This framework aims to manage the changing dynamics of the market and, at the same time, ensure organizational continuity into the unforeseeable future. The tendency of the organization to properly blend continuity and alternate characteristics has aided it in dominating the worldwide market. The company is constantly developing new principles to maintain leadership and avoid being carried away by competitors. This study delves into the strategic risk management of competition administration and internationalization of Tata Motors from India to the United Kingdom, a framework for extending automotive manufacturing operations into Nigeria.